2000
DOI: 10.1046/j.1365-2796.2000.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary arteriovenous malformations (PAVMs) and occurrence of neurological symptoms in patients with hereditary haemorrhagic telangiectasia (HHT)

Abstract: Abstract. Kjeldsen AD, Oxhùj H, Andersen PE, Green A, Vase P (Odense University and Odense University Hospital, Odense; University of Aarhus, Aarhus; and the Department of Otorhinolaryngology, Svendborg, Denmark). Prevalence of pulmonary arteriovenous malformations (PAVMs) and occurrence of neurological symptoms in patients with hereditary haemorrhagic telangiectasia (HHT). J Intern Med 2000; 248: 255±262.Background. Hereditary haemorrhagic telangiectasia (HHT) is a dominantly inherited disease. HHT is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 24 publications
5
78
0
4
Order By: Relevance
“…Microspheres were detected in the epicardium of the left ventricle in two of our exercising dogs, suggesting that recruitment of I-P shunts could play a role in embolic heart disease. In addition, previous work has shown that stroke patients have a higher prevalence of patent foramen ovale (38)(39)(40), and hereditary hemorrhagic telangiectasia patients are more susceptible to embolic stroke and neurologic symptoms (41), indicating that blood flow bypassing the pulmonary microcirculation may have important physiological relevance. Isolated lung work has shown that I-P arteriovenous shunts are up to 420 m in diameter in the dog (11), 390 m in the cat (9), and 200 m in the adult human (13).…”
Section: Shunt Consequencementioning
confidence: 99%
“…Microspheres were detected in the epicardium of the left ventricle in two of our exercising dogs, suggesting that recruitment of I-P shunts could play a role in embolic heart disease. In addition, previous work has shown that stroke patients have a higher prevalence of patent foramen ovale (38)(39)(40), and hereditary hemorrhagic telangiectasia patients are more susceptible to embolic stroke and neurologic symptoms (41), indicating that blood flow bypassing the pulmonary microcirculation may have important physiological relevance. Isolated lung work has shown that I-P arteriovenous shunts are up to 420 m in diameter in the dog (11), 390 m in the cat (9), and 200 m in the adult human (13).…”
Section: Shunt Consequencementioning
confidence: 99%
“…3 It is the right-to-left shunt between the pulmonary artery and pulmonary vein which is the fundamental defect, 3 allowing the passage of paradoxical emboli into the systemic circulation, bypassing the pulmonary capillary filter. [4][5][6] The patient' s peripheral oxygen saturation will be typically low and as expected does not normalise with an increase in FiO 2 . 3 In contrast to other AVMs, PAVMs do not affect cardiac haemodynamics and cardiac output is usually within normal limits 3 or, due to a low pulmonary vascular resistance, is even associated with supranormal cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Легочные АВМ наблюдаются у 15-50% больных НГТ [26][27][28]. В то же время, наличие артериовеноз ных шунтов в легких в 80-90% является проявлени ем болезни Рандю-Ослера-Вебера [28,29].…”
Section: клиника и диагностикаunclassified
“…Наиболее часто поражаемыми отдела ми ЖКТ являются желудок и тонкая кишка [27,39]. Большинство телеангиэктазий бессимптомны или вызывают клинически незначимые кровотечения [40].…”
Section: клиника и диагностикаunclassified